Bioremediasi Cacing Merah (Tubifex tubifex) dalam Pengolahan Air limbah - Achmad Taufik; Nadyawatie Warganegara (Poltekkes Kemenkes Bandung, 2013)
This stüdy tried to üşe red worms (tubifek tubifek) in wastewater treatment mainly domestic wastewater and slaughterhouse wastewater (Slaughterhouse RPH) that have a high content of organik matter Because red worms (Tubifek tubifek) is the most dominant macroinvertebrate and widely spread whose presence indicates that location was contaminated with organik materials. The purpose of this stüdy was to determine the effects of bioremediation red worms (Tubifek tubifek) in wastewater treatment, bioremediation to determine the effects of each type of waste is domestic waste water and sewage RPH. The results showed the effects of bioremediation of red worms (Tubifek tubifek) against domestic waste water up to day - 3 is the initial pH: 7.2 down to 6.9; initial BOD: 19.3 mg / I down to 15.1 mg / I Total initial N: 76.6 mg / I decreased to 26.1 mg / l; detergent initial: 0.76 mg / I down to 0.49 mg / l; initial PV: 13.35 mg / I menajdi 11 , 88 mg / I and initial TTS: 135 mg / I up to 149 mg / l. While the effects of bioremediation red worms (Tubifek tubifek) for wastewater abattoir until the day - 3 is the initial pH: 6.88 up to 7.37; initial BOD: 25.1 mg / I down to 20.1 mg / I Total initial N: 74.2 mg / I down to 16.6 mg / l; detergent initial: 0.57 mg / I down to 0.43 mg / l; initial PV: 134.57 mg / I to 114 , 96 mg / I and initial TTS: 145 mg / I up to 149 mg / l. The variation of the parameter values obtained during the observation time of 6-8 days in addition due to the activity of red worms is largely influenced by the activity of self furificatin of the waste water because most contain bacteria - bacteria that occur naturally decomposition. Need more research on the üşe of red worms (Tubifek tubifek) to treat wastewater in accordance with the life cycle and habitat of more specific so as to obtain effective duration üşe.